An Innovative and Secure Platform for Leveraging the Blockchain Approach for Online Exams - Albert Manawar (Aptisi Transactions On Technopreneurship (ATT), 2023)
Numerous educational establishments now use the online platform to conduct tests, particularly for students at the secondary and tertiary levels. Candidates are given a username and password by the most popular online test program, and they then log in to the designated page to answer the questions. However, there are numerous flaws in this system, and cheating on the test can be done by misusing the password. This demonstrates the significance of implementing a secure system to avoid this issue. A blockchain framework that safeguards the online examination system is presented in this paper. An educational data-connecting data management system has been secured using the proposed framework. Without the need for a copy from the central servers, institutions can simply compile their data history. Data security is improved and any potential for cheating between users or third-party institutions that access applications and services is eliminated by the proposed blockchain framework. This study provides a secure framework for conducting and evaluating subject tests to guarantee consistency between students and servers and secure questionnaire delivery from servers.